Clinical and epidemiological characteristics resistant hypertension in the practice of family doctor - S. V. Busel (Journal of Education, Health and Sport, 2017)
Busel S.V. Clinical and epidemiological characteristics resistant hypertension in the practice of family doctor. Journal of Education, Health and Sport. 2016;6(11):702-714. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.225448